PERAN DIGITALISASI DALAM MENDORONG PENINGKATAN PENDAPATAN PELAKU INDUSTRI KREATIF DI KABUPATEN SITUBONDO - Alindi Ristianti; Cinantya Sitaresmi; Zainul Mursyidin; Raya Aditya Pratama (Fakultas Ekonomi dan Bisnis, 2025)
This study examines the role of digitalization in strengthening the creative economy ecosystem in Situbondo Regency, focusing on its impact on productivity, market expansion, and increased income for creative industry players. Using qualitative descriptive methods, this research collected data through field observations, interviews, reports, and supporting literature to analyze four key pillars of digital ecosystem development: digital infrastructure investment, collaboration-based digital literacy, administrative incentives, and the formation of local digital clusters. The results indicate that approximately 70% of creative actors still face barriers to digitalization due to limited internet access and a lack of shared digital facilities. Collaborative digital literacy programs, involving the government, universities, and creative associations, have proven more effective than theoretical seminars, particularly in improving skills in content production, market management, and digital branding. Administrative support in the form of easy NIB (National Identity Card) registration, halal certification, and easy market access have also accelerated business growth and expanded market reach. Furthermore, the formation of local digital clusters is an important strategy to encourage collaboration, innovation, and the regeneration of creative talent through the provision of shared facilities and integrated networks. Based on the Triple Helix theory and Porter's cluster concept, this study confirms that transforming the digital creative industry requires a systematic and integrated approach, encompassing aligned policies, capacity building, and cross-sector synergy. If implemented consistently, this strategy has the potential to increase competitiveness, open global markets, and contribute to the growth of Indonesia's digital economy